Plasma preptin levels in patients with type 2 diabetes mellitus - Kalayci, Mehmet; Halifeoglu, Ihsan; Kalayci, Hatice; Ugur, Kader; Yilmaz, Musa (Kare Publishing, 2019)
Objectives: Diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia, and the prevalence is rapidly increasing worldwide. Preptin is a novel molecule with a metabolic effect that is secreted from pancreatic beta cells along with insulin. There are currently few studies about preptin in patients with type 2 DM (T2DM). This study was designed to observe differences in the plasma preptin level in patients with T2DM in comparison with a control group. Methods: The study included 82 patients with T2DM (mean age: 49.00±5.97 years; 42 females, 40 males) and 65 healthy individuals (mean age: 41.98±5.62 years; 31 females, 34 males). The patients with T2DM were divided into 2 groups: those newly diagnosed and those previously diagnosed and in treatment. The previously diagnosed group was further separated into 2 groups based on their glycated hemoglobin (HbA1c) level: a well-controlled DM (HbA1C value <7%) group and a poorly controlled DM (HbA1C value >7%) group. The chemistry parameters were analyzed with an Advia 1800 analyzer (Siemens Healthineers, Erlangen, Germany), and hormonal parameters were analyzed with an Immulite 2000 analyzer (Siemens Healthineers, Erlangen, Germany). Plasma preptin levels were measured using the enzyme-linked immunosorbent assay method. Results: Patients with newly or previously diagnosed T2DM had significantly higher glucose, HbA1c, insulin, homeo-static model assessment of insulin resistance (HOMA-IR), total cholesterol, triglyceride, low-density lipoprotein choles-terol, and preptin values (p<0.001 for each), and significantly lower high-density lipoprotein cholesterol levels com-pared with the control group (p<0.001). The preptin level demonstrated a positive correlation with insulin, HOMA-IR, HbA1c, and glucose levels (for control group: r=0.452-p=0.000, r=0.472-p=0.000, r=0.389-p=0.001, r=0.286-p=0.021, respectively; for T2DM group: r=0.484-p=0.000, r=0.544-p=0.000, r=0.288-p=0.009, r=0.236-p=0.033, respectively). Conclusion: The observed correlation between preptin level and DM a suggests that this peptide may have a possible role in the pathogenesis of DM, which may be particularly valuable, given that DM is a major public health problem. © 2018 by International Journal of Medical Biochemistry.
Keywords: Diabetes mellitus; insulin resistance; preptin